ChemInform Abstract: Asymmetric Preparation of New N, N‐Dialkyl‐2‐amino‐1, 1, 2‐triphenylethanol Catalysts and a Kinetic Resolution in the Addition of Diethylzinc to Flavene‐3‐carbaldehydes. Issue 28 (21st June 2013) - Kang, Seock Yong; Baek, Jinho; Ko, Yi Kyung; Im, Chan; Park, Yong Sun
Abstract The novel catalysts (I) and (II) are prepared and derivative (Ia) is found to be the most efficient one for the addition of ZnEt2 to aldehydes.